Pengaruh Profitabilitas, Leverage, Pertumbuhan Penjualan dan Ukuran Perusahaan Terhadap Penghindaran Pajak Pada Perusahaan Property dan Real Estate yang Terdaftar di BEI Tahun 2017-2020 - Ersa Nur Anggraeni; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The purpose of this study is to analyze the impact of profitability, leverage, sales growth and company size on tax avoidance in property and real estate sector companies listed on the Indonesia Stock Exchange in 2017-2020. Samples that meet the criteria by using the purposive sampling method collected 44 companies. The data processing technique uses the E-views version 10 application program. The results of this study partially confirm that profitability, leverage, sales growth, and company size have no significant effect on tax avoidance.